Pengaruh Sikap, Norma Subjektif, dan Kendali Perilaku terhadap Niat Kepatuhan Pegawai IAIN Surakarta dalam Membayar Zakat - Mei Candra Mahardika (UIN Raden Mas Said Surakarta, 2020)
Zakat is an obligation for Muslims who have more wealth. The results of the study in 2011 by BAZNAS and FEM IPB found the fact that the potential for zakat in Indonesia reached 217 trillion, while from that potential could only collect 1.729 trillion. This study used the planned behaviour theory from Ajzein and Fizbein which states attitudes, subjective norms, and behavioral control have a relationship with the intention. The study formulation looked at the determinants of IAIN Surakarta employees intentions in paying zakat. This study used a quantitative approach with a survey method using a questionnaire instrument. The population in this study were 445 employes of IAIN Surakarta. The samples of the study were 159 employes who were alreday civil servants. The data analysis techniques were quantitative descriptive and inferential descriptive. The result of the study explained that there was a relationship between attitudes, subjective norm, and behavioural control with the intention of IAIN Surakarta employees in paying zakat. Behaviour control has the highest relationship with intention. The behaviour in paying zakat carried out by IAIN Surakarta employees cannot be separated from the role of institution that use internal policies to encourage their employees to carry out zakat obligations. The existence of the Zakat Management Unit (UPZ) facilitates the collection and management of zakat from IAIN Surakarta employees themselves. The influence of co-workers also increases the understanding of religion, especially the obligation of zakat for employees who have civil servant status, because their income has reached nisab (limit) to pay zakat.